Conducting clinical trials with self-collection of pharmacokinetic samples: Experience from an exploratory, phase 1, open-label trial of centanafadine SR in healthy individuals - Chelsea Ye; Tatiana Shablinski; Susan E. Shoaf; Chris Chung; Michelle Bullock (Contemporary Clinical Trials Communications)
Background: The COVID-19 pandemic accelerated a shift to decentralized clinical trials. We present the potential feasibility of this approach from a phase 1 pharmacokinetic (PK) trial. Methods: Healthy adults (18–55 years) with a body mass index of 19.0–32.0 kg/m2 were enrolled. The trial comprised a screening period, 2 clinic visits (visits 1, 2), 2 at-home visits (visits 3 and 4), and follow-up clinic visit (visit 5). Participants received a single 100-mg oral dose of centanafadine sustained release at visits 1, 2, and 4. Pharmacokinetic samples, electrocardiograms (ECGs; 6-lead [participant] and 12-lead [staff]), and vital signs were collected by clinical personnel (visit 1), under staff supervision (visit 2), and remotely (visit 4), facilitated by the Verily clinical trial application. Successful sample collection at visit 4 was reported descriptively. A survey assessed the utility of training, devices, and the Verily app, and ability to complete trial procedures. Results: Among 20 participants enrolled, 90 % were female, mean (SD) age was 35.9 (11.1) years. Verily platform/procedures facilitated successful remote vital sign collection in at least 75 %, ECGs in at least 80 %, and blood microsamples in 65 %–70 % of participants at visit 4. Most agreed that training was adequate, and they were able to complete trial procedures on their own. Participants favored self-collection over staff collection, having visits in their own location, and would consider participation in similar future research. Conclusions: Results from this decentralized PK trial, with remote, in-home sample collection and monitoring, demonstrated the potential feasibility of this study design.